Formação continuada de professores de matemática no estado do Paraná a partir do Projeto Folhas - Parcianello, Juliane (2015)
The Project Papers was an action of Continuing Education for Elementary School teachers in the state of Paraná, developed by the State Education Secretary among 2003 and 2010. This research had as main aim to understand the contribution of the Project Papers for the Continuing Education of Mathematics teachers. It was developed by the analysis of official documents from SEED/PR (Resolutions, Instructions, Work Plans) that guide the Continuing Education acts regarding the formation and appreciation of the educational workers and of texts published by the Secretary, through a parallel among those and the social, political and economic context in which they were designed and presented to the teachers and the community in general. The analysis was enlarged to thirty Papers written about the structuring content Functions and it was held by fifteen questionnaires with the teachers/authors and two questionnaires with the Pedagogical Team Coordinators of the Educational Regional Core of Dois Vizinhos and Pato Branco. The results showed that the Project Papers enabled Mathematics teachers access to the research in order to enlarge their knowledge, as well the collaborative production of texts in theoretical and methodological character about the curriculum contents targeted to the High School students. There was, with the Papers, stimulus to the professional career, through the punctuation to the functional progression. It is evidenced that the Project Papers, in the Mathematics area, was an important proposal that was set as a teaching tool and of Continuing Education for teachers. It enabled the Mathematics teachers the opportunity of formation, through the written production, of the validation process and of the use of the material, both to the teacher who brought it forth and to the one who makes use of the teaching material. The Project Papers built a meaningful alternative for the Continuing Education of Mathematics teachers in the state of Paraná.